Induction and Growth of Endosperm Cali of Rimau Gerga Lebong (RGL) Citrus on Several Media Compositions - Sari, Rossi Anandayu; Herawati, Reny; Herison, Catur (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2019)
Rimau Gerga Lebong (RGL) variety is one of the main orange fruit commodities in Lebong Regency of Bengkulu Province, which has a competitive advantage and has good market potential. However, high number of seed characteristic makes this orange fruit becomes less popular. Triploid genotype formation through endosperm culture in vitro is an alternative solution to develop seedless orange fruit. The objective of this study was to determine the best composition medium for callus induction of endosperm of RGL orange seeds as the foremost step of in vitro triploid plant development. The research was conducted from August 2017 until December 2018 at the Plant Tissue Culture Laboratory, Department of Agronomy, Faculty of Agriculture, University of Bengkulu. The experiment was arranged in a completely randomized design, with eight treatment combinations i.e. G1 (MT + 5 ppm BAP + 2 ppm 2,4-D), G2 (MT + 5 ppm BAP + 2 ppm 2,4-D + 500 ppm CH), G3 (MT + 5 ppm BAP + 2 ppm 2,4-D + 500 ppm + 0.5 ppm Kinetin), G4 (MT + 5 ppm BAP + 2 ppm 2,4-D + 500 ppm CH + 0.5 ppm to 500 ppm Kinetin + ME) , G5 (MS + 5 ppm BAP + 2 ppm 2,4-D), G6 (MS + 5 ppm BAP + 2 ppm 2,4-D + 500 ppm CH), G7 (MS + 5 ppm BAP + 2 ppm 2,4- D + 500 ppm CH + 0.5 ppm Kinetin), G8 (MS + 5 ppm BAP + 2 ppm 2,4-D + 500 ppm CH + 0.5 ppm to 500 ppm Kinetin + ME), with three replications. The experimental unit was five culture bottles containing three explants per bottle. Observations were conducted on days to callus formation, rate of callus formation, callus weight, callus diameter, callus color and texture. The results showed that media of MS + 5 ppm BAP + 2 ppm 2,4-D + 500 ppm CH was the best media for callus induction, and MT + 5 ppm BAP + 2 ppm 2,4-D + 500 ppm CH was the best media for callus development.Keyword: RGL citrus, calli, endosperm, kinetin, BAP